CFD analysis on the intensified mechanism of gas-liquid mass transfer in a microporous tube-in-tube microchannel reactor. (January 2022) - Li, Wen-Ling; Wang, Jian-Hong; Chen, Han; Shao, Lei; Chu, Guang-Wen; Xiang, Yang
Highlights: CFD-Eulerian model was validated with experimental data and empirical correlations. The effects of operating conditions and structures on the mass transfer were analyzed. The gas-liquid mass transfer mechanism in the annular microchannel was revealed. The entrance-effect zone was determined based on the turbulent kinetic energy dissipation rate. Abstract: A three-dimensional CFD model coupled with a mesoscale mass transfer model was developed to simulate the absorption of CO2 in the microporous tube-in-tube microchannel reactor (MTMCR). The simulation results were validated by experimental data and empirical correlations, with the discrepancies within ±20%. The local breakage and coalescence of the gas-liquid interfaces enhanced mass transfer in the annular microchannel. The higher Re G and Re L means lower ratio between energy for mass transfer and surface, and also, larger contribution of interfacial area to the mass transfer. Additionally, an entrance-effect zone was revealed, and the entrance-effect zone enlarged with the increase in Re G and Re L . The overall mass transfer coefficient and entrance-effect zone enlarged significantly with appropriate decrease in the length of the gas-liquid collision zone. Results of this work could provide a theoretical basis for the further optimization of MTMCR.